The Implementation of Telepharmacy in Bangka Belitung Islands Province - Djuria, Rachmawati Felani; Andrajati, Retnosari; Syafhan, Nadia Farhanah; Wispriyono, Bambang (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Telepharmacy is a telemedicine health service in the pharmaceutical sector that uses telecommunications to assist patients located far away during the Covid-19 pandemic. Furthermore, professional organizations are responsible for continuously providing information to pharmacists, ensuring they stay updated with the latest developments in the field. Mobile applications have emerged as the primary medium through which information can be accessed. Therefore, this research aimed to determine the implementation of telepharmacy in the Bangka Belitung Islands Province using observational research with a qualitative approach. The participants comprised a total of 11 individuals and the technique employed was purposive sampling. Subsequently, the collected data were subjected to analysis using the Miles and Huberman model. The results showed that the utilization of telepharmacy commenced within Bangka Belitung Islands Province and the community pharmacy service implemented the concept in the form of Drug Information Services, drug consultation or patient counseling, and prescription services through e-prescribing. Additionally, field observations highlighted the presence of services such as home delivery of medicines, patient education, and online non-cash payments. The implementation of telepharmacy within hospitals remains absent, despite the widespread adoption of digital services facilitated by the SIMRAS application. Pharmacists also ensured the administrative compliance of their colleagues through the utilization of the SIAP application. The preliminary stages of the implementation commenced in the Bangka Belitung Islands Province.